Investigating the Role of Non-Governmental Organisations in Green Energy Innovations and Sustainable Practice in Lagos State, Nigeria - Bamidele Olajide; Loveth Walker; Victor Ojakorotu (E-Journal of Humanities, Arts and Social Sciences)
This paper investigates the role of Non-Governmental Organizations (NGOs) in green energy and sustainable practices provision in Lagos State, Nigeria. Given the huge energy deficit in the state and its impacts on the socioeconomic dynamics of the state, the study, dwelling on the blending of theoretical assumptions of stakeholder theory and Ecological Modernization Theory and qualitative research design found that NGOs are central to the efforts of Lagos State government in promotion of renewable energy adoption and other sustainable practices. Data for the study was collected through in-depth interviews with 15 NGOs working in the area of green energy and sustainability practices. The study found that NGOs have recorded relative success stories in green energy innovation and continue to be strategic partners to government and other sustainability stakeholders in mobilizing the grassroots for green energy adoption. It concludes that the efforts of NGOs in green energy innovations and sustainability practices adoption are fraught with challenges, including financial inadequacy, bureaucratic delays, and low cooperation from communities, among others. The recommends that the government and other stakeholders, among others, should strengthen their support towards the activities of NGOs in green energy adoption to reduce carbon footprints and enhance the socioeconomic dynamics of the states. This study emphasises the strategic roles NGOs can play in helping the government achieve its energy transition and sustainability goals in Lagos State.